2022
DOI: 10.1038/s41467-022-33502-7
|View full text |Cite
|
Sign up to set email alerts
|

Multicellular immune dynamics implicate PIM1 as a potential therapeutic target for uveitis

Abstract: Uveitis is a severe autoimmune disease, and a common cause of blindness; however, its individual cellular dynamics and pathogenic mechanism remain poorly understood. Herein, by performing single-cell RNA sequencing (scRNA-seq) on experimental autoimmune uveitis (EAU), we identify disease-associated alterations in cell composition and transcriptional regulation as the disease progressed, as well as a disease-related molecule, PIM1. Inhibiting PIM1 reduces the Th17 cell proportion and increases the Treg cell pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 71 publications
1
24
0
Order By: Relevance
“…Studies on Jun , Bst2 , and Klf6 have indicated the involvement of these molecules in a variety of tumors [ 48 51 ]. Pim1 has been reported to regulate the differentiation of T and B cells [ 52 , 53 ]. Pim1 also promotes Cxcr4 cell surface expression, thus regulating cell migration [ 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…Studies on Jun , Bst2 , and Klf6 have indicated the involvement of these molecules in a variety of tumors [ 48 51 ]. Pim1 has been reported to regulate the differentiation of T and B cells [ 52 , 53 ]. Pim1 also promotes Cxcr4 cell surface expression, thus regulating cell migration [ 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…Patients with AU often suffer from persistent inflammation caused by autoimmune‐mediated damage to the targeted retinal and uveal tissues 3,4 . Utilizing multi‐omics approaches, accumulated studies have demonstrated immune disturbance in the eyes of AU cases 5–7 . However, the precise mechanism underlying dynamic alterations of the intraocular immune microenvironment in the initiation and progression of AU is still not fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been shown recently that Pim1/Pim2 deficiency prevented mTORc1 activation and the proliferation of nonconventional intra-epithelial gut CD8 T lymphocytes (IEL) in response to the cytokine IL-15 (James et al, 2021). Elevated PIM kinase expression has been noted in patient T cells for a number of autoimmune conditions, including rheumatoid arthritis, uveitis and coeliac disease, and PIM kinase inhibition has been proposed as a possible intervention to dampen autoimmunity (James et al, 2021;Maney et al, 2021;Li et al, 2022). PIM kinase inhibitors have also entered clinical trials to treat some cancers and there is active interest in combining these with immunotherapies (Clements and Warfel, 2022).…”
Section: Introductionmentioning
confidence: 99%